2010
DOI: 10.1111/j.1464-5491.2010.03027.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiac autonomic neuropathy and hypertension and its potential influence on diabetic complications

Abstract: These data are strongly in favour of the role of cardiac autonomic neuropathy in hypertension in diabetic patients. The association of the cardiac autonomic neuropathy/hypertension profile with vascular complications is consistent with a deleterious effect on vascular hemodynamics and structure, additional to the effects of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 32 publications
7
35
1
6
Order By: Relevance
“…In contrast to previous studies [36], only a trend was observed in the present study between higher microalbuminuria levels and the presence of CAN, as detected by low RR E/I ratios. This may have been due to the relatively small number of subjects with microalbuminuria, which could be explained by the fact that T1DM patients with hypertension were excluded from our present study, whereas recent observational data have favoured the role of CAN in hypertension of T1DM patients [39]. Furthermore, the association of the CAN/hypertension profile with vascular complications is consistent with deleterious effects on vascular haemodynamics and structure in addition to the effects of hypertension itself.…”
Section: Discussionsupporting
confidence: 49%
“…In contrast to previous studies [36], only a trend was observed in the present study between higher microalbuminuria levels and the presence of CAN, as detected by low RR E/I ratios. This may have been due to the relatively small number of subjects with microalbuminuria, which could be explained by the fact that T1DM patients with hypertension were excluded from our present study, whereas recent observational data have favoured the role of CAN in hypertension of T1DM patients [39]. Furthermore, the association of the CAN/hypertension profile with vascular complications is consistent with deleterious effects on vascular haemodynamics and structure in addition to the effects of hypertension itself.…”
Section: Discussionsupporting
confidence: 49%
“…Alterations of several intertwined functional elements, such as inflammation (28), impaired endothelial function (29), dysfunctional leptin (30), and ghrelin regulation (31), might be involved, leading to an increase in sympathetic activity, a reduction of cardiac baroreflex sensitivity, and facilitating an increase in arterial pressure (32). Hypertension has been found to be a predictor of CAN in type 2 diabetes in cross-sectional studies (33)(34)(35)(36), whereas the use of antihypertensive drugs was associated with autonomic indexes in the Hoorn Study (34). Consistent with this evidence, our patients with CAN were more frequently treated for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The term 'microvascular complications' usually refers to nephropathy, retinopathy, or leg ulceration, although many complications of diabetes involve contributions from both microvascular and macrovascular disease. For example, autonomic neuropathy may contribute to hypertension, 7 which is itself a powerful risk factor for heart disease, stroke and peripheral arterial disease. 8,9 Conversely, the presence of the metabolic syndrome increased the risk of microvascular complications among 415 diabetic patients managed within primary care.…”
mentioning
confidence: 99%